Magnetically Tunable Graphene-Based Terahertz Metasurface - Lu, Yafeng; Wang, Chen; Zhao, Shiqiang; Wen, Yongzheng (Frontiers in Physics, 2021)
Graphene is a promising platform for configurable terahertz (THz) devices due to its reconfigurability, but most researches focus on its electrical tunability. Here, we propose a graphene-based THz metasurface comprised of graphene cut-wire arrays for magnetic manipulation of the THz wave. With the external magnetostatic field applied, the resonant currents of the graphene cut-wire can be effectively affected by the Lorentz force, leading to an evident tuning of the response of the metasurface. The simulated results fully demonstrate that the resonance frequencies of the graphene THz metasurface can be efficiently modulated under a vertical magnetostatic field bias, resulting in the manipulation of the transmission and phase of the THz wave. As a new method of the tunable THz metasurface, our structure shows promising applications in the THz regime, including the ultracompact THz modulators and magnetic field sensors.